Fixed Points of Quadratic Contractions in Dislocated Quasi B-Metric Spaces and with an Application - M. V. R. Kameswari (New Trends in Physical Science Research Vol. 7, 2022)
The goal of this study is to show fixed point theorems in the framework of dislocated quasi b-metric spaces for a self-map meeting specific contraction conditions involving quadratic terms. These findings are also applied to a pair of weakly compatible self-maps. As a result, we deduce application to a differential equation and suitable examples are also furnished in support of our results. Our findings unify and enrich the comparable results in the literature.